The Effectiveness of Acceptance and Commitment Therapy on Traumatic Memory Syndrome and Physical Syndrome in Female-Headed Households - Haji Mashhadi, Bahareh; Khajvand Khoshli, Afsaneh; Aasdi, Javanshir (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of acceptance and commitment-based therapy on traumatic memory syndrome and physical syndrome in female-headed households. Method: The research method was quasi-experimental or pre-test, post-test and follow-up with a control group. The statistical population of the study includes all female-headed households in Tehran in 2019 that 24 people were selected as a sample using available sampling method and were divided into two groups of 12 people, acceptance and commitment therapy group and control group. Acceptance and commitment treatment protocol (Hayes et al., 2005) was performed on the experimental group in eight 90-minute sessions, but the control group remained on the waiting list. Analysis of variance with repeated measures and SPSS software were used to analyze the data. Results: The results showed that acceptance and commitment-based therapy on traumatic memories syndrome (F=38.86, P